The clip and the tip: Lessons learned from ablation of atrial fibrillation in patients postpercutaneous mitral valve repair. (21st May 2019) - Rottner, Laura; Lemes, Christine; Dotz, Inge; Wohlmuth, Peter; Schmidt, Tobias; Mathew, Shibu; Heeger, Christian‐H.; Reissmann, Bruno; Fink, Thomas; Rillig, Andreas; Frerker, Christian; Ouyang, Feifan; et al.
Abstract: Background: Atrial fibrillation (AF) and higher grade mitral valve regurgitation are often associated. For both, there are interventional therapeutic options such as pulmonary vein isolation (PVI) and percutaneous mitral valve repair (PMVR) using MitraClip. Objective: This study investigated the feasibility, safety and clinical outcome of AF ablation in patients with prior PMVR. Methods: This study included patients with symptomatic AF who underwent PVI after prior PMVR at a tertiary care center (14 consecutive patients, group I). A propensity‐score matched group of 42 patients (1:3 matching, group II) without prior valve repair acted as controls. Results: Acute PVI was achieved in all patients. No difference was found regarding median procedure time (group I: 125.0 [Q1: 120.0; Q3: 176.3] vs group II: 135.0 [120.0; 177.5] minutes; P = 0.87) and median fluoroscopy duration (group I: 17.2 [12.9; 25.9] vs group II: 18.6 [12.3; 25.9] minutes; P = 0.95). In group I, one patient suffered a postprocedural transient ischemic attack. No further major complications occurred ( P = 0.25). No periprocedural interference with the MitraClip was noted. The Kaplan‐Meier estimate 18‐month overall arrhythmia‐free survival after the index procedure including a 3‐month blanking period was 64.8% (95% confidence interval [CI] 42.1‐99.8%) for the study group and 68.3% (95% CI, 54.6‐85.6%) for the control group P = 0.35). A higher percentage of left atrial tachycardias was observed in the study group (67% vs 12% of patients with any arrhythmia recurrence; P = 0.01). Conclusion: Catheter ablation of AF in patients with prior PMVR is feasible and safe and results in satisfying clinical outcome.